Stan realizacji programu SAPARD w województwie małopolskim - Siekierski, Jan (Current State of SAPARD Programme Implementation in the Małopolska Voivodship, 2005)
The work presents the current state of SAPARD Programme implementation in the Malopolska voivodship. Provincial units of the Agency for Restructuring and Modernisation of Agriculture implement the programme and are its paying agencies. Four measures constituing the structure of SAPARD Programme are discussed against a background of the situation of agriculture in the region.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 2, s. 262-269